Modeling the hydrodynamics of the OWC device placed over an undulated seabed in the presence of ocean current - Santanu Kumar Dash; Kshma Trivedi; Santanu Koley; Shrabani Mondal (Alexandria Engineering Journal)
The current investigation emphasizes the mathematical modeling of the hydrodynamics associated with the oscillating water column wave energy converter (OWC-WEC) device situated above undulating bottom of the ocean in the presence of ocean currents. The mathematical problem is investigated within the framework of the two-dimensional Cartesian coordinate system by incorporating the classical linear wave-structure theory. The boundary element method is used to address the corresponding boundary value problem. A significant attention is devoted to the analysis of the effectiveness and horizontal wave force exerted on the frontal barrier of the oscillating water column device by considering various values of incident wave and current parameters, as well as structural parameters related to both the oscillating water column device and the undulated seabed. Moreover, the study in the time domain is carried out in order to illustrate the variations in free surface elevations at different time instances by considering the influence of both following and opposing currents. The results demonstrate that the “Doppler Shift” effect of the frequency due to the presence of ocean currents significantly influences the resonating patterns of the efficiency and force curves. As the current velocities increase, the resonating frequencies occur for higher values of incident wavenumbers.